2011
DOI: 10.1007/s00421-011-2112-z
|View full text |Cite
|
Sign up to set email alerts
|

High volume of endurance training impairs adaptations to 12 weeks of strength training in well-trained endurance athletes

Abstract: The purpose of the present study was to compare the effect of 12 weeks of strength training combined with a large volume of endurance training with the effect of strength training alone on the strength training adaptations. Well-trained cyclists with no strength training experience performed heavy strength training twice a week in addition to a high volume of endurance training during a 12-week preparatory period (S + E; n = 11). A group of non-strength trained individuals performed the same strength training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 49 publications
7
51
1
2
Order By: Relevance
“…Prior to any trials, assessment of ̇O 2max and 1RM loads were performed for the purpose of normalising relative training intensity, all assessments were conducted in line with standardised procedures 20,21 . Upon commencing the study, participants attended the laboratory in a fed state.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to any trials, assessment of ̇O 2max and 1RM loads were performed for the purpose of normalising relative training intensity, all assessments were conducted in line with standardised procedures 20,21 . Upon commencing the study, participants attended the laboratory in a fed state.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that large volumes of endurance training reduce strength training adaptations (e.g. Hickson 1980;Kraemer et al 1995;Rønnestad et al 2011b). It may therefore be hypothesized that the rather small improvement in 1RM deep squat in the present study was due to the combination of a small strength training volume and a large endurance training volume on leg muscles.…”
Section: Submaximal Treadmill Rollerskiingmentioning
confidence: 99%
“…However, combining large volumes of endurance training with heavy strength training seems to reduce the hypertrophic response to strength training (e.g. Aagaard et al 2011;Kraemer et al 1995;Losnegard et al 2011;Rønnestad et al 2011b). It is therefore of interest to further investigate the eVect of combining heavy strength training with large volumes of endurance training on muscle thickness and muscle strength and how it aVects vertical jump performance, body mass, and endurance performance in Nordic Combined athletes.…”
Section: Introductionmentioning
confidence: 97%
“…It is also to an extent the basis of Block Periodization. 7,48,[50][51][52][53][54][55][56][57][58] The follow-up to this article will further detail the benefits of Block periodization through a discussion on how concentrated loads are sequenced and timed. Furthermore, this review will provide evidence on how periodizing the training plan through block programming can augment the strength and power characteristics required for most track and field events.…”
Section: Article In Pressmentioning
confidence: 99%